Desain Lembaga Peradilan Sengketa Pemilihan Kepala Daerah di Indonesia Untuk Mewujudkan Keadilan Demokrasi dan Keadilan Konstitutional - Susilo, Tri (Fakultas Syariah INSURI Ponorogo, 2023)
The implementation of direct regional head elections has been going on for two decades. The problem so far is the dispute resolution institution, until now the regional head election dispute settlement in Indonesia is still divided into several institutions such as the General Election Supervisory Board, the State Administrative Court, the District Court, and the Supreme Court, the Constitutional Court, each court has its own procedures, causing miscoordination and overlapping of powers. This article aims to find out the design of regional head election dispute justice institutions in Indonesia to realize democratic justice and constitutional justice. This research is a normative legal research with a statutory, analytical, and case approach that aims to find out the background of the idea of establishing a special court for regional head elections in Indonesia to realize democratic and constitutional justice. The settlement of post-conflict local election disputes in Indonesia is the antithesis of the weaknesses and problems in resolving regional head election disputes, which have been going on for two decades, namely: disputes over the settlement of election processes and results by several judicial institutions. This is to provide the best as an alternative special court for the resolution of regional election disputes in the future. This research resulted in the finding that the regional head general election judiciary is something that must be considered in the Indonesian constitutional system, which institutionally will be equivalent to the Constitutional Court and the Supreme Court, nominally it is also something new, namely called the General Election Court. This institution simplifies the dispute resolution process for regional head elections and general elections to realize constitutional justice